Imiquimod cream improves photodamaged skin - Suliman S Alfaraj; Yasser A Ghobara; Abdullah M Aleisa (Wolters Kluwer Medknow Publications, 2022)
Chronic exposure to ultraviolet light causes wrinkles and dyspigmentation. Imiquimod cream is an immune-modulator medication approved for the treatment of genital warts, actinic keratosis, and superficial basal cell carcinoma. Few scientific papers were published in the literature on the effect of imiquimod on photodamaged skin. We report four patients with benign and malignant cutaneous neoplasms who were treated with 5% imiquimod cream and noticed improvement in their skin appearance. We believe that imiquimod cream is a safe and effective option for improving photodamaged skin with excellent safety profile.